Idosos portadores de doença renal crônica: o papel da gestão em saúde na cidade de Santa Maria - Rodrigues, Bruno Vinicius (2022)
This study sought to identify how the process of renal failure in the elderly proceeded and the responses of municipal health management in the municipality of Santa Maria. In this sense, the qualitative methodology was used, the discussion was based on the dialectical-critical method through the epistemological analysis of the reality proposed by Marx, since the analysis and interpretation of the data were based on the analysis of the discourse proposed by Gagneten. So, in this study, we verified the implications of the world of work in the daily life of the interviewees and how chronic diseases emerged and remained, generating a process of kidney injury throughout the lives of these people. The absence of a public, universal, health system, before the creation of the Unified Health System, as well as the absence of public policies aimed at prevention and health promotion, were decisive for the interviewees' illness process. In addition, it was evidenced that chronic diseases such as Diabetes Mellitus and Hypertension were neglected throughout the life trajectory of the subjects analyzed, either because of the routine of life totally focused on the world of work, not observing the care inherent to these health conditions, either by insufficient coverage of access to health. In this sense, we were able to verify the relevance of Primary Care actions for these patients, since patients with Diabetes Mellitus and Systemic Arterial Hypertension unconditionally need support from public policies for promotion, prevention and self-care for the maintenance and control of their respective situations of health. However, it was also possible to understand that the process of illness resulting from the aforementioned underlying pathologies took place gradually and, above all, silently. Consequently, we also identified the low coverage of primary care in the city of Santa Maria and the difficulty of referral to specialized care as preponderant factors in the process of renal failure. Thus, with the lack of assistance from primary care for these workers, disabling diseases such as Chronic Kidney Disease end up silently emerging during the aging process, culminating in the loss of kidney function and the need for hemodialysis treatment to maintain life.